Heuristic based evolution for the coordination of autonomous vehicles in the absence of speed lanes - Kala, Rahul; Warwick, Kevin (Applied soft computing, 2014)
•Traffic operating in the absence of lanes is capable of larger traffic bandwidths.•Fast genetic algorithm with Bezier curve generates the trajectory of each vehicle.•Overtaking and vehicle following behaviours are studied for unorganized traffic.•These behaviours are fused as heuristics to make a fast coordination scheme.•Plans are adapted to overcome uncertainties as the vehicles move. The current state of the art in the planning and coordination of autonomous vehicles is based upon the presence of speed lanes. In a traffic scenario where there is a large diversity between vehicles the removal of speed lanes can generate a significantly higher traffic bandwidth. Vehicle navigation in such unorganized traffic is considered. An evolutionary based trajectory planning technique has the advantages of making driving efficient and safe, however it also has to surpass the hurdle of computational cost. In this paper, we propose a real time genetic algorithm with Bezier curves for trajectory planning. The main contribution is the integration of vehicle following and overtaking behaviour for general traffic as heuristics for the coordination between vehicles. The resultant coordination strategy is fast and near-optimal. As the vehicles move, uncertainties may arise which are constantly adapted to, and may even lead to either the cancellation of an overtaking procedure or the initiation of one. Higher level planning is performed by Dijkstra's algorithm which indicates the route to be followed by the vehicle in a road network. Re-planning is carried out when a road blockage or obstacle is detected. Experimental results confirm the success of the algorithm subject to optimal high and low-level planning, re-planning and overtaking.